Brief Report: High Programmatic Isoniazid Preventive Therapy (IPT) Use in Pregnancy Among HIV-Infected Women. (1st September 2019) - LaCourse, Sylvia M.; Wagner, Anjuli D.; Cranmer, Lisa M.; Copeland, Audrey; Maleche-Obimbo, Elizabeth; Richardson, Barbra A.; Matemo, Daniel; Kinuthia, John; John-Stewart, Grace
Abstract : Background: The World Health Organization recommends isoniazid preventive therapy (IPT) for people living with HIV (PLHIV) to prevent tuberculosis (TB), including pregnant women. Recent trial results suggest increased adverse pregnancy outcomes associated with IPT during pregnancy. Data are limited regarding programmatic IPT use in pregnant PLHIV. Methods: We assessed previous programmatic IPT during pregnancy among HIV-infected mothers on enrollment to an infant TB prevention trial in Kenya. Pregnancy IPT use was assessed by the estimated conception date assuming 38 weeks of gestation. Correlates of initiation and completion were analyzed by relative risk regression, using generalized linear models with log link and Poisson family adjusted for IPT initiation year. Results: Between August 15, 2016, to June 6, 2018, 300 HIV-infected women enrolled at 6 weeks postpartum. Two hundred twenty-four (74.7%) women reported previous IPT, of whom 155/224 (69.2%) had any pregnancy IPT use. Forty-five (29.0%) initiated preconception extending into early pregnancy, 41 (26.5%) initiated and completed during pregnancy, and 69 (44.5%) initiated in pregnancy and extended into early postpartum. The median gestational age at IPT pregnancy initiation was 15.1 weeks (interquartile range 8.3–28.4). Pregnancy/early postpartum IPT initiation was associated with new pregnancy HIV diagnosis [adjusted relative risk 1.9 95% confidence interval (CI): 1.6 to 2.2, P < 0.001]. Six-month IPT completion rates were high [147/160 (91.9%)] among women with sufficient time to complete before trial enrollment and similar among preconception or during pregnancy initiators [adjusted relative risk 0.93 (95% confidence interval: 0.83 to 1.04, P = 0.19)]. Conclusions: Programmatic IPT use was high in pregnant PLHIV, with frequent periconception and early pregnancy initiation. Programmatic surveillance could provide further insights on pregnancy IPT implementation and maternal and infant safety outcomes. Abstract : Supplemental Digital Content is Available in the Text.